2018
DOI: 10.1080/2162402x.2018.1548241
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hedgehog signaling reprograms the dysfunctional immune microenvironment in breast cancer

Abstract: Host responses to tumor cells include tumor suppressing or promoting mechanisms. We sought to detail the effect of Hedgehog (Hh) pathway inhibition on the composition of the mammary tumor immune portfolio. We hypothesized that Hh signaling mediates a crosstalk between breast cancer cells and macrophages that dictates alternative polarization of macrophages and consequently supports a tumor-promoting microenvironment. We used an immunocompetent, syngeneic mouse mammary cancer model to inhibit Hh signaling with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 56 publications
5
70
0
Order By: Relevance
“…Although a recent report has suggested a role for lactic acid in functional polarization of TAMs (14), the molecular pathways required for TAM M2 polarization in vivo remain largely unknown. A previous study has implicated the important role of Hh signaling in reprogramming the TME to facilitate tumorigenesis through TAMs in breast cancer (38). Our observations provided further evidence that the Hh signaling pathway in TAMs is critical for their M2 polarization to promote tumorigenesis.…”
Section: Tams On Neoplastic Progression (4-8)supporting
confidence: 78%
“…Although a recent report has suggested a role for lactic acid in functional polarization of TAMs (14), the molecular pathways required for TAM M2 polarization in vivo remain largely unknown. A previous study has implicated the important role of Hh signaling in reprogramming the TME to facilitate tumorigenesis through TAMs in breast cancer (38). Our observations provided further evidence that the Hh signaling pathway in TAMs is critical for their M2 polarization to promote tumorigenesis.…”
Section: Tams On Neoplastic Progression (4-8)supporting
confidence: 78%
“…Besides immunity, ingenuity pathway analysis (IPA) suggested that the hedgehog pathway might have a role in NCWS. It is worthwhile to mention that a few studies demonstrated the involvement of hedgehog pathway in celiac disease and alteration of immune surveillance in cancer development [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, M2 macrophages are stimulated by Th2 cytokines such as transforming growth factor β 1 (TGF-β 1 ), IL-4 and IL-13 [87], which activate STAT6 target genes [88] (suppressing immune system functions) and promote tumor cell proliferation. M2 TAMs are the most frequent type in breast cancers [89] since during carcinogenesis TME most likely drives M1 to the M2 phenotype [90]. It is well known that macrophages are recruited to the tumor by a range of chemokines (including vascular endothelial growth factor, VEGF, and C-C chemokine ligand 2) and foster breast cancer progression in different ways: regulating stroma invasion and cell intravasation [91,92], promoting angiogenesis [93] and metastasis [94,95], and remodeling extracellular matrix (ECM) by metalloproteinase secretion [96].…”
Section: Macrophagesmentioning
confidence: 99%